Portable digital holographic camera featuring enhanced field of view and reduced exposure time. (February 2021) - Kumar, Raj; Dwivedi, Gaurav; Singh, Omendra
Highlights: Portable digital holography based camera with laser source and digital sensor array integrated on a mechanical platform. 192% increase in field of view compared to conventional digital holographic system. Achieved performance of tripod mount digital holographic camera. Reduction in exposure time to counter the vibration effects during recording process. Abstract: Digital holography offers a full-field and high-resolution technique for non-destructive testing and inspection of electro-opto-mechanical components and products. But as holography is an interference-based technique so environmental and system vibrations put requirement for development of holographic systems in laboratory on optical vibration isolation platforms. Another drawback associated with digital holography is its small field of view due to limited spatial resolution of the available digital sensors. In this work, we report design, realization and validation of a compact and portable digital holographic camera (DHC) with enhanced field of view. We used an efficient opto-mechanical design to simultaneously increase the field of view and reduce exposure time and hence the effect of vibrations. The field of view of proposed DHC is 192% more compared to that of conventional digital holographic system. The temporal stability of the developed DHC is measured to be 48 nm over an operation time of 10 min. This development may enable use of digital holography for wide range of non-destructive testing applications.